(untitled) (Dissertare, 2022)
The following essay has as an objective to analyze the definition and manifestations of workplace sexual harassment in the context of gender violence and identify myths that tend to naturalize such labor harassment situations, from the enterprise sphere. The nature of workplace sexual harassment is highlighted as a phenomenon framed in power relations, which constitutes a form of gender violence and it is based on stereotypes about the assignment of roles between men and women. Among the conclusions, it stands out that workplace sexual harassment is a health and safety problem at work and that, therefore, preventive actions can be considered, in addition to policies and procedures for reporting these behaviors.